Targeting the N Terminus of eIF4AI for Inhibition of Its Catalytic Recycling. Issue 10 (17th October 2019) - Jiang, Chenxiao; Tang, Yegen; Ding, Lulu; Tan, Renke; Li, Xiaojing; Lu, Junyan; Jiang, Jing; Cui, Zhaomeng; Tang, Zhewei; Li, Wei; Cao, Zhangjun; Schneider-Poetsch, Tilman; et al.
Summary: DEAD-box ATP-dependent helicases (DEAH/D) are a family of conserved genes predominantly involved in gene expression regulation and RNA processing. As its prototype, eIF4AI is an essential component of the protein translation initiation complex. Utilizing a screening system based on wild-type eIF4AI and its L243G mutant with a changed linker domain, we discovered an eIF4AI inhibitor, sanguinarine (SAN) and used it to study the catalytic mechanism of eIF4AI. Herein, we describe the crystal structure of the eIF4AI-inhibitor complex and demonstrate that the binding site displays certain specificity, which can provide the basis for drug design to target eIF4AI. We report that except for competitive inhibition SAN's possible mechanism of action involves interference with eIF4AI catalytic cycling process by hindering the formation of the closed conformation of eIF4AI. In addition, our results highlight a new targetable site on eIF4AI and confirm eIF4AI as a viable pharmacological target. Graphical Abstract: Highlights: SAN, a natural product, directly inhibits eIF4AI's enzymatic activity The first co-crystal structure of the eIF4AI-inhibitor complex SAN blocks the conformational change of eIF4AI Abstract : The natural product sanguinarine interferes with the catalytic cycle of eIF4AI through binding to its N terminus. Sanguinarine impedes the formation of the closed conformation of eIF4AI and inhibits its catalytic cycle and protein synthesis in vitro and in vivo .